Impact of the fishery for late-larval European sardine (Sardina pilchardus) on the adult stock in the Adriatic Sea. (26th December 2016) - Carpi, Piera; Morello, Elisabetta B.; Uriarte, Andres; Panfili, Monica; Roel, Beatriz; Santojanni, Alberto; Donato, Fortunata; Arneri, Enrico
Abstract : Bianchetto ["white" late-larval and juvenile stages ('fry') mainly of sardine ( Sardina pilchardus )] was fished traditionally along most of the Italian coast. The Gulf of Manfredonia (southwest Adriatic Sea) hosts a sardine nursery which was historically exploited by the bianchetto fishery using trawlnets; the fishery was banned in 2010. Here, we model this larval fishery under different assumptions of catch and natural mortality to assess its impact on the adult sardine stocks in the Adriatic Sea. The results show that the impact of the fishery is heavily dependent on the choice of early-stage natural mortality. The model proposed by Pepin (1991). Effect of temperature and size on development, mortality, and survival rates of the pelagic early life history stages of marine fish. Canadian Journal of Fisheries and Aquatic Sciences, 48: 503–518. was selected as the most plausible. Under this assumption, the direct effect of the bianchetto fishery in the Gulf of Manfredonia on the Adriatic adult sardine stock appears to be low, but not negligible, with impacts estimated as a 0.1–2% increase in the numbers of sardine at age 1 in the absence of a bianchetto fishery. Projections show that a 5% impact on age 1 sardine may be sufficient to bring the adult stock below safe levels. Therefore, given the uncertainties surrounding the impact assessment and the current status of the stock, if this fishery were to be resumed, catches should be kept at the lowest possible level until the underlying processes are better understood.